Analyzing the Socioenactive Dimensions of Creative Learning Environments with Preschool Children - Carbajal, Marleny Luque; Baranauskas, Maria Cecília Calani (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Several published papers discuss how to encourage creativity in the classroom. An emerging concept is creative learning, which attempts to understand, experiment, and define methodologies and learning environments designed to promote creativity. Enaction theorists, a new thread of cognitive science, understand that cognition and creativity always emerge through real-time interaction with the environment and other agents in that environment. Socioenactive systems are extensions to the enactive system concept, bringing attention to socio-cultural values in the dynamic coupling of the human (through the body senses) and technology. This work aims to explore and understand the creative process of preschool children during their interaction with a tangible programming environment (TaPrEC+mBot) that allows programming of a robot car by arranging wooden blocks. The analysis draws on the physical, digital, and social dimensions of socioenactive systems. The results show that the children felt especially involved through their bodies and engaged in the activity of creating their own programming scenario. They also suggest that the children’s reasoning and behavior seem to be connected or influenced by their body movements and their physical, social and digital experience and interaction with the tangible programming environment.